Effect of YouTube Videos and Pictures on EFL Students’ Writing Performance - Styati, Erlik Widiyani (Dinamika Ilmu, 2016)
This research aims at investigating the effect of YouTube videos and pictures as the authentic materials on EFL Indonesian students’ writing performance. The experimental research is conducted by using quasi-experimental design. This research employs two groups experimental. This is comparing two groups to see which one is effective to be used in helping the students in writing. The first group is employed by using YouTube videos and the second group is treated by using pictures. Both of YouTube and pictures are the authentic materials which help the students to have better writing performance. The subjects are the second semester students of English Department, IKIP PGRI Madiun. Both of the groups, the students are asked to write paragraph by using YouTube videos and pictures as the authentic materials. The data are analyzed by using Independent t-test. The result of the study shows that there is significantly different between the students who write paragraph after being treated by using YouTube videos and by using pictures as the authentic materials. The students who are treated by using YouTube videos have lower writing performance than the students who are treated by using pictures. The mean of the students who write paragraph after being treated by using YouTube videos as authentic materials is lower than those who are treated by using pictures. This means that using pictures in writing are better than using YouTube videos to help the students in writing performance.